PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PERDAGANGAN KOTA SEMARANG - Nurcahaya Sinaga; Susi Sulandari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The key of success on the organization depends on interaction and coordination among employees when reach the organization’s goals. Human resources the movers of the other resources. When the human resources are working, it determines how the organization reach the goals. The problem on this research is how the influence of motivation and discipline to the employee’s performance in the Tradieng office of Semarang City. The aim on this research to know the influence between motivation and discipline to employee’s performance. This research used explanatory quantitative method and the respondents on this resarch are the employee’s on Trading Agency of Semarang Ciy. The method of collecting data are interview and questionnaire. The analysis technique on this research using Rank Kendall correlation. According to the result of the research, the employee’s performance are very good, motivation and discipline are good. The correlation test showing that motivation do not have any relation and influence to the employee’s performance, the discipline have a relation to the employee’s performance, while the motivation and the discipline have a relation to the employee’s performance but in a weak condition.